2010
DOI: 10.1007/s00167-010-1058-8
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic torn discoid lateral meniscus in adults

Abstract: The purposes of this study were to report degenerative changes that coexist with a symptomatic torn discoid lateral meniscus in adults and to analyze the factors associated with the accompanied degenerative changes. From 1997 to 2008, 329 knees in the 305 patients were included. Associations between the status of the meniscus and the coexisting degenerative changes on the images and the arthroscopic findings were statistically analyzed. Marginal osteophyte was seen on conventional radiography in 118 patients (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 18 publications
(27 reference statements)
2
52
0
Order By: Relevance
“…But this finding is not supported by other studies including our study. Ahn et al [4] analyzed the factors associated with the severity of the marginal osteophyte formation on the conventional radiography using multivariate analysis, and they failed to prove this relationship. Similarly, Asik et al Bold p values with (*) represent significant correlation Musculoskelet Surg [14] compared the clinical results of patients who underwent arthroscopic saucerization before and after 12 months of presentation and again failed to show a significant difference.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…But this finding is not supported by other studies including our study. Ahn et al [4] analyzed the factors associated with the severity of the marginal osteophyte formation on the conventional radiography using multivariate analysis, and they failed to prove this relationship. Similarly, Asik et al Bold p values with (*) represent significant correlation Musculoskelet Surg [14] compared the clinical results of patients who underwent arthroscopic saucerization before and after 12 months of presentation and again failed to show a significant difference.…”
Section: Discussionmentioning
confidence: 97%
“…drozkankose@hotmail.com however, the incidence of DLM is reported between 0.4 and 16.6 % in patients who underwent knee arthroscopy [3,4]. Clinical manifestations of lateral discoid meniscus are highly variable depending on the type of the discoid meniscus, the presence of an accompanying tear and the status of rim stability.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Deie et al reported the relationship between the type of osteochondritis dissecans and the type of DLM. Ahn et al suggested a significant correlation between the type of discoid meniscus and the accompanying chondral lesions in their univariate analysis. Kim et al also reported that there is a significant difference between the outcome and the type of DLM or the type of meniscectomy.…”
Section: Discussionmentioning
confidence: 99%
“…A discoid meniscus is an anatomical congenital anomaly which was considered to be a vestige of viviparous cartilage development of the knee (1,2). Diagnosis of the discoid meniscus has been improved by the MRI technique, and the incidence of discoid lateral meniscus of the knee in the Chinese population is 16–46% (3).…”
Section: Introductionmentioning
confidence: 99%